Cytokines Disregulation in Birds and Mammals Infected by Avian Influenza Virus - Dyah Ayu Hewajuli; NLPI Dharmayanti (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2016)
Highly Pathogenic Avian Influenza (HPAI) virus causes severe dysfunction in nervous system lead to mortality in birds and mammals. The innate immunity plays an important role as initial barrier against the infection that stimulated by recognition of pathogens through Toll like Receptor (TLR). TLR activates Nuclear Factor-kappa B cascade pathway. Cytokines are mediators to initiate, proliferate and regulate inflammation against the virus infection. They are classified according to their activities or target cells, such as interferons, interleukins, chemokines, colony stimulating factor, and tumor necrosis factors. The gene expression of cytokine was found in different organs of chicken and mammals infected with HPAI and Low Pathogenic Avian Influenza (LPAI) virus to express immune response against infection. The HPAI and LPAI viruses cause up-regulated and down-regulated cytokines, disruption of cell mediated immune response lead to increased AI virus pathogenicity. The objective of this review is to describe disregulation mechanism of cytokines that increase AI virus pathogenicity in birds and mammals.